2010
DOI: 10.1105/tpc.109.071803
|View full text |Cite
|
Sign up to set email alerts
|

The ABORTED MICROSPORES Regulatory Network Is Required for Postmeiotic Male Reproductive Development in Arabidopsis thaliana    

Abstract: The Arabidopsis thaliana ABORTED MICROSPORES (AMS) gene encodes a basic helix-loop-helix (bHLH) transcription factor that is required for tapetal cell development and postmeiotic microspore formation. However, the regulatory role of AMS in anther and pollen development has not been fully defined. Here, we show by microarray analysis that the expression of 549 anther-expressed genes was altered in ams buds and that these genes are associated with tapetal function and pollen wall formation. We demonstrate that A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
357
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 287 publications
(375 citation statements)
references
References 90 publications
(139 reference statements)
15
357
2
1
Order By: Relevance
“…3). This phenotype is distinct from other tapetal mutants that have been described, such as Arabidopsis ams (Xu et al, 2010) and rice tdr (Li et al, 2006) mutants, which exhibit tapetal defects involving swelling of the tapetum as a consequence of vacuole increase rather than cytoplasmic proliferation. Subsequent to this proliferation, very rapid degeneration of the tapetum and microspores occurs in ptc1 via necrosis-like breakdown.…”
Section: Ptc1 Determines a Conserved And Diversified Switch Of Apoptocontrasting
confidence: 59%
See 1 more Smart Citation
“…3). This phenotype is distinct from other tapetal mutants that have been described, such as Arabidopsis ams (Xu et al, 2010) and rice tdr (Li et al, 2006) mutants, which exhibit tapetal defects involving swelling of the tapetum as a consequence of vacuole increase rather than cytoplasmic proliferation. Subsequent to this proliferation, very rapid degeneration of the tapetum and microspores occurs in ptc1 via necrosis-like breakdown.…”
Section: Ptc1 Determines a Conserved And Diversified Switch Of Apoptocontrasting
confidence: 59%
“…Tapetal cell development and differentiation are critical for the early events in male reproduction, including meiosis; however, during late pollen development, tapetal degeneration, triggered by an apoptosis-like process, is also vital for viable pollen formation (Papini et al, 1999;Varnier et al, 2005;Li et al, 2006;Aya et al, 2009). Currently, although several genes encoding putative transcription factors have been reported to be associated with tapetal function and degeneration, such as Arabidopsis (Arabidopsis thaliana) MYB33/MYB65 (Millar and Gubler, 2005), DYSFUNCTIONAL TAPETUM1 (DYT1; Zhang et al, 2006), ABORTED MICROSPORE (AMS; Sorensen et al, 2003;Xu et al, 2010), and MALE STERILITY1 (MS1; Wilson et al, 2001;Ito and Shinozaki, 2002) and rice (Oryza sativa) GAMYB (Kaneko et al, 2004;Aya et al, 2009;Liu et al, 2010), UNDEVELOPED TAPETUM1 (UDT1; Jung et al, 2005), TAPETUM DE-GENERATION RETARDATION (TDR; Li et al, 2006), and MADS3 (Hu et al, 2011), their detailed functional roles in regulating tapetal PCD during anther development are unclear. We have shown that the Arabidopsis ms1 mutant displays altered tapetal development, with a lack of normal PCD and abnormal tapetal degeneration associated with large autophagic vacuoles and mitochondrial swelling (Vizcay-Barrena and Wilson, 2006).…”
mentioning
confidence: 99%
“…Given that AMS, the Arabidopsis ortholog of TDR, directly regulates the expression of AtABCG26, the Arabidopsis ortholog of OsABCG15 ( Xu et al, 2010), we propose that TDR may act as the direct regulator of OsABCG15, which remains to be elucidated.…”
Section: Transcriptional Analysis Of Genes Related To Lipid Metabolismentioning
confidence: 99%
“…Some plant ABCG proteins have been reported to contribute to the synthesis of extracellular barriers. In Arabidopsis, ABCG11 (Cuticular Defect and Organ Fusion1/DESPERADO/White-Brown Complex11; Bird et al, 2007;Panikashvili et al, 2007Panikashvili et al, , 2010, ABCG12 (Eceriferum5/WBC12; Pighin et al, 2004), ABCG13 (Panikashvili et al, 2010), ABCG29 (Alejandro et al, 2012), ABCG32 (Bessire et al, 2011), and ABCG26 (WBC27; Xu et al, 2010;Quilichini et al, 2010Quilichini et al, , 2014Choi et al, 2011;Dou et al, 2011) have been shown to be involved in transport of lipidic compounds. Notably, it has been reported that these ABCG proteins have a broad substrates spectrum (for example, ABCG11 transports both cutin and wax monomers, and ABCG13 and ABCG32 mainly transport cutin monomers, whereas ABCG12 mainly transports wax precursors, and ABCG29 mainly transports monolignol).…”
mentioning
confidence: 99%
See 1 more Smart Citation